Українсько-польські наукові зв’язки у гуманітарній сфері (за матеріалами наукової доповіді на засіданні Бюро Відділення історії, філософії та права НАН України 27 листопада 2014 року) - Литвин, М.Р. (Вісник НАН України, 2015)
Проаналізовано українсько-польські зв’язки у гуманітарній сфері за останні 20 років. Розглянуто основні напрями і тематику досліджень в установах Польської академії наук, Національної академії наук України та університетах обох країн. Відзначено необхідність відновлення діяльності Польсько-української історичної комісії при ПАН і НАН України, а також перейняття українськими науковцями та представниками влади напрацювань Інституту національної пам’яті Польщі щодо декомунізації історичної пам’яті, вшанування жертв тоталітарних режимів, проведення документальних пошуків та правових експертиз. Проанализированы украинско-польские научные связи в гуманитарной сфере за последнее двадцатилетие. Особое внимание обращено на исследование археологов обеих стран о заселении территории современной Украины в древнейший период, реконструкцию путей миграций и переселений в неолите и раннем бронзовом веке, анализ культурных связей древнего населения Прикарпатья и Волыни. Показаны основные направления и тематика исторических исследований в учреждениях Польской академии наук, Национальной академии наук Украины и университетах двух стран, касающиеся в том числе и вопросов, которые вызывают дискуссии в обществе. Обобщены исследования этнологов, филологов и культурологов относительно трансформаций традиционной культуры в условиях пограничья, показаны особенности этнокультурной интеграции населения Украины и Польши. Отмечена необходимость возобновления деятельности Польско-украинской исторической комиссии при ПАН и НАН Украины, а также заимствования украинскими учеными и представителями власти опыта Института национальной памяти Польши по декоммунизации исторической памяти, увековечению памяти жертв тоталитарных режимов, проведению документальных поисков и правовых экспертиз. The article analyses cooperation between Polish and Ukrainian academic institutions in the field of humanities in the recent two decades. It focuses on archaeological research of the early settlements on the territories that are now Ukraine and mutual cultural influences of Prykarpattia and Volhynia population, as well as archaeological reconstruction of Neolithic and Bronze Age migration routes conducted by scholars of both countries. The article also examines main directions and issues of historical research of the Polish Academy of Sciences (PAS), the National Academy of Sciences (NAS) of Ukraine and universities of both countries with an emphasis on problematic issues that attract attention in both societies. It summarizes results of ethnologists, linguists, literature and culture students research on transformations of traditional culture on the borderland and specific features of ethnic and cultural integration of Ukrainian and Polish population. The argument is made about the necessity to resume activities of the Polish-Ukrainian Historical Committee affiliated with PAS and NAS of Ukraine. The article suggests that Ukrainian academia and authorities should adopt the best practices of Polish Institute of National Remembrance regarding dealing with decommunization of historical memory, commemorating victims of totalitarian regimes, conducting and legal expert evaluations.